Inventory Control of Lubricating Oil Raw Materials with Silver Meal Heuristic Method at PT. Alp Petro Industri - Pasuruan - Enny Aryanny; Dwi Prasetyo; Rizqi Novita Sari (Nusantara Science and Technology Proceedings, 2022)
Alp Petro Industri is a company engaged in the lubricating oil industry. The raw materials needed are Feed Stock, Base Oil, and Additives. PT. ALP Petro Industri experienced problems in its inventory, which sometimes experienced excess inventory which resulted in high storage costs, and sometimes experienced a shortage of raw materials which resulted in the cessation of the production process so that the company could not fulfill the products desired by consumers. This study aims to determine the level of inventory control of lubricating oil raw materials at PT. Alp Petro Industri Pasuruan optimally to minimize inventory costs. The existing data in the company has the characteristics of varying demand levels, so it is processed with a dynamic deterministic inventory control model, namely the Heuristic Silver Meal method. From the calculation of the total cost of inventory with the company's method of IDR. 50,722,980,000 while the Heuristic Silver Meal method is IDR. 50,536,660,000. The Heuristic Silver Meal method produces a total cost of inventory that is cheaper than the company's method of IDR. 50,722,980,000 with a savings of IDR. 186.320.000. The optimal number of orders for raw materials for Feed Stock raw materials is 348,697 kg per month, Base Oil raw materials are 408,733 kg per month, and Additives raw materials are 141,783 kg per month.